Identifikasi Masalah Kerusakan Produk Air Mineral Kemasan Gelas Dengan Pendekatan Peta Kendali Atribut - Wibowo , Heri; Anggraini, Melani; Sitompul , Julkipli (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
PT. Tirta Nauli Sibolga was a manufacturer of dringking water in a pack and supplying that product to all region of Sibolga. In it production the manufacturer still expertence a problem with the presence of defective product in every production that has not reached zero defect. P control chart can be defined to help detect any irregularities that occur in the bottled water product, by applying the control limits (UCL, CL, LCL). The results of the scatter diagram there 3 points that deviate, where 3 points that are observed 24,25 and 29. And then be revised to eliminate the data that have adefect smaller than LC or greater than LCL. The measurement data based on the Pareto diagram, that there are 2 types of damage that dominates damage is high enough that cup volume. The fishbone diagram determines the cause of disability occurred, disability that occured was due to factors of machine, material, human, enironmental and methods, the highest failure is when production runs are impaired or dispenser machine error. To attempt repair of the problem it is necessary to check the condition of the machine before the production process.